Feeding cities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Food for the Cities. Food Supply and Distribution Policies to Reduce Urban Food Insecurity. A Briefing Guide for Mayors, City Executives and Urban Planners in Developing Countries and Countries in Transition By O Argenti, FAO, Food into cities collection